2000
DOI: 10.7748/ns2000.05.14.37.34.c2846
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture and consultant nurse outcomes: part 2 nurse outcomes

Abstract: This new culture had a positive impact on the unit in which it was based, on practitioners and their practice, and also on the trust. A number of factors, including transformational leadership, other facilitative processes, expertise in the practice of nursing, and other subroles of the consultant nurse were shown to be influential. Part one, published last week, described the concept of organisational culture. This article discusses the consultant nurse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 18 publications
2
71
0
1
Order By: Relevance
“…The educational domain of APN, discussed by many authors (i.e. Walters, 1996; Scott, 1999; Manley, 2000; Dawson & Spence, 2001; Darmody, 2005; Woodward et al ., 2005; Fairley & Closs, 2006; Wolf & Robinson‐Smith, 2007; Manley et al ., 2008; Baldwin et al ., 2009; Mitchell et al ., 2010; Jannings et al ., 2011), consists of formal education, informal education, being an educational resource, and strategic level of education. Advanced practice nurses are perceived as experts in education, and the total working time in this domain varies, on average, from 20% to 26% (Dawson & Spence, 2001; Charters et al ., 2005; Mayo et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The educational domain of APN, discussed by many authors (i.e. Walters, 1996; Scott, 1999; Manley, 2000; Dawson & Spence, 2001; Darmody, 2005; Woodward et al ., 2005; Fairley & Closs, 2006; Wolf & Robinson‐Smith, 2007; Manley et al ., 2008; Baldwin et al ., 2009; Mitchell et al ., 2010; Jannings et al ., 2011), consists of formal education, informal education, being an educational resource, and strategic level of education. Advanced practice nurses are perceived as experts in education, and the total working time in this domain varies, on average, from 20% to 26% (Dawson & Spence, 2001; Charters et al ., 2005; Mayo et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Although management activities have been identified in many studies as part of the APN role (Walters, 1996; Scott, 1999; Dawson & Spence, 2001; Dawson & McEwen, 2005; Woodward et al ., 2005; Dawson & Coombs, 2008), there was less enthusiasm about it being important to the APN role (i.e. Woodward et al ., 2006; Jinks & Chalder, 2007); the emphasis rather remaining on leadership aspects (Manley, 2000; Woodward et al ., 2005; Abbott, 2007; Jinks & Chalder, 2007; Redwood et al ., 2007; Manley et al ., 2008; Baldwin et al ., 2009). Advanced practice nurses are well placed to provide leadership at both strategic and clinical levels (Manley et al ., 2008), which is a key mechanism for achieving and embedding transformation in practice (Manley, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through action research, Manley (2000) demonstrated how a consultant nurse in an Intensive Care Unit created a positive culture of change in the unit, introduced evidenced based care and multidisciplinary collaboration, empowered colleagues and developed practice. The key findings from this seminal piece of work strongly suggested that providing support, being patient centred, enabling development, active participation, and the development of decision-making was evident.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leadership is one of four key elements of the Consultant Nurse role (NHSE 1999) and is the key mechanism for achieving and embedding transformation in practice (Manley 1997, NHSE 1999, Manley 2000a,b, 2002, 2004a,b). Leadership is the main approach to enabling and developing a culture of effectiveness in the workplace (Manley 2004b), specifically at the micro‐systems level, that is, where most health care is experienced by patients and users and provided by the health care team (Manley & Webster 2006).…”
Section: Introductionmentioning
confidence: 99%